M. E. Church, 1911 - Wheeler, Indiana (4343374048) - Steve Shook from... (Wikimedia Commons, 2010)
Carte postale ancienne issue de Wikimedia Commons. Titre: M. E. Church, 1911 - Wheeler, Indiana (4343374048). M. E. CHURCH WHEELER IND Date: 1911 Source Type: Postcard Publisher, Printer, Photographer: Unknown Postmark: November 6, 1911, Wheeler, Indiana Collection: Steven R. Shook Remark: The following news item appears in the October 30, 1884, issue of the Porter County Vidette: WHEELER. The bell for the M. E. church asrived [sic] last Tuesday, and it is pronounced by good judges to be a fine one. We want it hung and ready next week Wednesday to ring out the election of J-i-m - - - B-l-a-i-n-e. Source: Porter County Vidette, Valparaiso, Porter County, Indiana | October 30, 1884 | Volume 28, Number 44, Page 4, Column 2. Column titled "Wheeler." Copyright 2010. Some rights reserved. The associated text may not be reproduced or transmitted in any form or by any means, electronic, mechanical, photocopying, recording, or otherwise, without prior written permission of Steven R. Shook.
Licence Creative Commons Attribution 2.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; port